Bound for the Second Hankel determinant of certain generalized class of close-to-Convex functions / Nur Syahira Rosman ... [et al.] - Rosman, Nur Syahira; Mazlan, Nurul Yasmin; Mohmad Azemi, Nor Syamimi; Yahya, Abdullah (UiTM Cawangan Negeri Sembilan, 2021)
Geometric function theory is a study about geometric properties of certain classes of analytic functions. There are many classes of functions in geometric function theory that have been introduced in this field of research.